Pengaruh Literasi Keuangan Dan Financial Technology Terhadap UMKM Di Kabupaten Malaka Kota Betun - Alisia Maria Mendes; Fransina W. Ballo; Maria Indriyani H. Tiwu (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study aims to determine the influence of Financial Literacy and Financial technology on MSMEs in Malaka Regency, Betun City, both partially and simultaneously. This study used a type of Quantitative Descriptive research and this research used an Associative approach. The sample in this study is 47 MSMEs in Betun City. The sampling technique uses the Simple Random Sampling method. The data collection technique in this study used the Questionnaire Dissemination technique with Likert Scale measurement scale. Data analysis techniques in this study use hypothesis tests (t test and F test), and Coefficient of Determination. Data management in this study uses SPSS (Statistical Product and Sevice Solution) software. The results of this study prove that Financial Literacy and Financial technology together have a positive and significant effect on MSMEs in Malaka Regency, Betun City.